THE CORRELATION OF THE ROLE OF SOCIETY ON NUTRITION CARE BY POSITIVE DEVIANCE MOTHER - Tri Ratna Ningsih; Chatarina Umbul W; Hari Basuki; Annis Catur (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Society has important role in helping poor mother who has under five child to give proper diet. The purpose of the research was to analyze the correlation of society role on nutrition care pattern by positive deviance mother from poor families in Mojokerto Regency East Java. This research design was using case control with case population that were poor mothers with healthy under-five and control population were poor mothers with nutritious problem under-five child. Number of case group samples were 78 people and control group were 41 people. Sampling technique used multi stage sampling. Data collection using questionnaires that have been tested validity and reliability test to 30 people. Data analysis using chi square statistic test. The result of this research showed that the role of society in positive deviance mothers is sufficient as much as 37 people (46.84%). In non-positive deviance the role of society is deficient as many as 35 people (85.37%). = 0.000 and value Î± = 0,05, meant there was relation of society role with pattern of nutrition care of positive deviance mother. The role of society made the mothers motivated to provide good nutrition in their under five children.